Controlled Growth of Metal‐Organic Frameworks on Polymer Brushes. Issue 54 (30th August 2017) - Hou, Liman; Zhou, Mingdong; Dong, Xiaozhe; Wang, Lei; Xie, Zhigang; Dong, Dewen; Zhang, Ning
Abstract: Polymer brushes are for the first time used to induce the synthesis of metal‐organic frameworks (MOFs). The semi‐fixed polymer chains provide a confined environment, which allows a mild growth of MOFs in between polymer chains to give surface‐attached spherical MOF nanoparticles, in contrast to the larger MOF cubes/plates formed simultaneously in solution. Polymer brushes bearing carboxylate acid functionalities are indispensable for the formation of surface bound MOFs, while no MOF nanoparticles are observed on neutral polymer brushes. Characterization of the resultant MOF/polymer brushes hybrid film indicates the formation of crystalline MOF structure. The dimension of surface‐attached MOFs can be fine‐tuned from 20 nm to 1.4 μm simply by varying the structural parameter of polymer brushes and the nucleation duration. The method is not only applicable to the synthesis of MOF‐5 and MIL‐125, but shows great potential for the preparation of other surface‐attached MOFs. Abstract : Brush it off : Tailored synthesis of MOFs in nanoscale dimension is challenging. Polymer brushes are demonstrated to be an efficient platform in controlling the MOFs size from several tens of nanometer to micrometer range simply by varying the structural parameters of polymer brushes.